The Impact of Green Space in Residential Yard - Shahril, Nur Ameera Syuhada Ainul; Shareh Musa, Sharifah Meryam; Zainal, Rozlin; Mohd Noh, Hamidun; Kassim, Narimah (Research in Management of Technology and Business, 2021)
The green space in residential area have been played an extremely important role in contributing to the quality of human health and environment. World Health Organization (WHO) website 2012 said that they had been doing the recent estimates show on the physical inactivity to poor of access to green area, account for 3.3% of global death. global deaths. “Developers must provide green space” said local council from The Star newspaper. Despite this, some evidence of the positive impacts of green spaces on health was found. The main objectives of this research is to study how green space boost the health qualities among residents in housing development, to study the development of green space in construction industry and to found out the effective improvement needed for green spaces in residential yard. This research had been successfully prove that green spaces really helps in boost health qualities among populations in residential area. There development of green spaces in residential yard are also follow some guideline provided. The respondents also gives the best effective improvement to be taken for the green spaces in residential yard. This study was being conducted in Malacca with mixed method in both quantitative and qualitative methods in the form of survey and interview respectively. The survey has been distributed to 200 respondents in Malacca but only 100 respondents managed in answering the survey. For the interview, there three respondents chosen but due to Covid-19 pandemic occurs in Malaysia, interview session can’t be done to prevent the virus spread. Therefore, the interview session is conducted by distribute the Google form survey only to the respondents.